Heat Transfer Enhancement in Single Heat Exchanger 2D Pipe Using Rod with Different Angles Based on Computational Fluid Dynamics Study - Ahmed Ali, Sarmad (Emerging Advances in Integrated Technology, 2025)
The current numerical study focuses on the statistical investigation of the airflow and the improvement of the heat transfer rate by forced convection of a single pipe in a heat exchanger by the inclusion of a rod. Using the finite volume method by numerical simulation the flow characteristics of the working fluid with enhanced heat transfer are numerically studied. Homogeneous heat flux is applied to the upper and lower walls of the pipe. More for the Reynolds number range (9000-18000) the effect of inserting a rod inside the tube at different oblique angles (40°,50°, and 60°) was examined. Numerical results revealed that the transfer coefficient rate (Nusselt number) increase in the tube inserted into the rod is higher compared to the normal pipe. In addition, the results also showed that when the angle of inclination of the rod in the single-pipe heat exchanger is gradually increased the Nusselt number increases. The Nusselt number maximum value was shown at the 60° angle of the rod insert. Because of the resistance of a bigger flow, the friction factor was found by using the rod inserts at (60°) and pitch distance (0.04 m). For a minimum slant angle of (40°) and a pitch distance of (0.04 m), the maximum value of the performance evaluation criteria (PEC) was stated. In comparison to the smooth tube, the percentage of fluid velocity distribution rises by (50,57, and 63%) at the angle of inclination of the rod (40°, 50°, and 60°), respectively